Sum of The Degrees of Dominating Set And Complementary Dominating Set Using Eulidean Division Algorithm of Divisor 5 For Interval Graph G - A, Sudhakaraiah; A, Venkateswarrao; T, Venkateswarlu; K, Narayana (International Journal of Computer Sciences and Engineering, 2019)
Interval graphs, their importance over the years can be seen in the increasing number of researchers trying to explore the field. The concept of the domination is a rapidly developing area in Graph Theory. In this paper, we tried to present some relations on the sum of degree of the vertices in dominating set and complementary dominating set using Euclidean division algorithm of divisor 5 for interval graph G.